Respon Semut Terhadap Kerusakan Antropogenik Pada Hutan Lindung Sirimau, Ambon - Fransina Latumahina (Agrologia, 2016)
The objective of field study was to study the response of ants to forest damage due to presence of human activities in Sirimau Conservation forest, Ambon. The respons of ants was analyzed based on their richness, abundance, diversity, frequency and functional response to anthropogenic damage by used of line transecting method. Secondary parameters measured were local microclimate as well as soil physical and chemical characteristics. The study found 23 species of ants and 16,601 individual ants in the forests; the highest species abundance was 0.158, while frequency and diversity index was 32.44% and 2.92 each and were classified as moderate. Functionally ants consisted of oppurtunist (1 species), generalized myrmicinae (1 species), specialist predators (4 species), tropical climate specialists (6 species), dominant dolichoderinae (4 species), subordinate camponitini (6 species) and criptic species (4 species). Anthropogenic activity contributed to forest habitat destruction through forest opening, logging, forest fires and shifting cultivation. Anthropogenic damage in secondary forest caused fragmentation and degradation, followed by inbalance of environment and ecosystem components